2018
DOI: 10.1016/j.jcmg.2017.01.025
|View full text |Cite
|
Sign up to set email alerts
|

CMR–Derived Extracellular Volume Fraction as a Marker for Myocardial Fibrosis

Abstract: These findings prove the theoretical concept of ECV as an estimate for diffuse myocardial fibrosis, but only in the absence of significant myocardial inflammation. Assuming that various degrees of myocardial inflammation and fibrosis coexist in such a scenario, the measured ECV will reflect a sum of these different pathologies but will not inform solely on the extent of diffuse fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 35 publications
1
46
0
2
Order By: Relevance
“…One previous study had demonstrated that in cases with coexisting inflammation and diffuse fibrosis, the ECV would reflect the sum of both pathologies [31]. ECV has shown excellent discriminative value in differentiating myocarditis patients from healthy subjects [21,32], and declined significantly with the recovery of myocarditis [21].…”
Section: Abbreviationsmentioning
confidence: 99%
“…One previous study had demonstrated that in cases with coexisting inflammation and diffuse fibrosis, the ECV would reflect the sum of both pathologies [31]. ECV has shown excellent discriminative value in differentiating myocarditis patients from healthy subjects [21,32], and declined significantly with the recovery of myocarditis [21].…”
Section: Abbreviationsmentioning
confidence: 99%
“…The fact that only ECV values were significantly different is probably based on that fact that the native T 1 signal including, besides the myocardium itself, blood flow, water, and fibrosis, whereas ECV is representing the extracellular space more exclusively, and therefore is more sensitive for fibrosis. 32 In a study by Ellims et al, ECV and not native T 1 was well correlated with ventricular stiffness in a transplant cohort. 33 In addition, we could show, within this small cohort, that there is a weak correlation between overall [ 11 C]mHED retention (regardless of the 7% cutoff defining a segment as reinnervated) and native T 1 times, as well as the percentage of ECV by MRI.…”
Section: Discussionmentioning
confidence: 92%
“…In our study, using mapping techniques and a 16‐segment myocardial model, segments with evidence of reinnervation by PET, mainly located on the anterior wall, showed nonsignificantly higher T 1 relaxation times and significantly higher ECV when compared with segments without evidence of reinnervation. The fact that only ECV values were significantly different is probably based on that fact that the native T 1 signal including, besides the myocardium itself, blood flow, water, and fibrosis, whereas ECV is representing the extracellular space more exclusively, and therefore is more sensitive for fibrosis . In a study by Ellims et al, ECV and not native T 1 was well correlated with ventricular stiffness in a transplant cohort …”
Section: Discussionmentioning
confidence: 96%
“…Our prospective single-center study represents a substudy from the Magnetic Resonance Imaging in Myocarditis (MyoRacer) trial (ClincialTrials.gov registration no. NCT02177630), including 44 of 129 originally reported consecutive participants (7,17). This prior article evaluated patients with acute and chronic myocarditis by using LLC and T1 and T2 mapping, whereas the present article reports the application of TA on T1 and T2 mapping not reported previously.…”
Section: Methodsmentioning
confidence: 97%